Innovative characteristics of users' intention to continue using personalized recommendation news apps - Chen, Yijie; Mohd Zawawi, Julia Wirza; Yaakup, Hani Salwah (Human Resource Management Academic Research Society, 2022)
With the massive increase in the available news information, it is difficult for users to quickly obtain the news they are interested in, resulting in personalized recommendation news applications. As the popularity of such innovative products grows, it is important to understand how people perceive and use these innovations. The focus of this study was the personalized recommendation news app "Toutiao," which has a high level of user activity in China. Based on the diffusion of innovation theory, this study investigates the relative advantages, compatibility, complexity, and observability characteristics of the Toutiao App as independent variables (IV). The dependent variable is the users' intention to continue using (DV) products. Furthermore, the research on innovation characteristics will help developers and service providers of mobile news apps in determining which innovations are more capable of attracting and retaining users, as well as which innovations have specific reference significance for the improvement of user experience mechanisms and market development strategies.